On-line monitoring of ambient hydrocarbon concentrations - Marnane, Ian Sean (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2001)
The result of a comprehensive set of hydrocarbon measurements undertaken at an urban roadside, rural and industrial site in Ireland are presented. Very little reported data on ambient hydrocarbon measurements were previously available. There was a notable lack of short-term measurements, which are particularly useful for characterising the sources and behaviour of ambient hydrocarbon concentrations.
Keywords: Civil Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin